THE APPLICATION OF DEMONSTRATION METHOD WITH ANIMATION MEDIA TO IMPROVE LEARNING ACTIVITY AND ACHIEVEMENT OF KOPLING SYSTEM SERVICE OF TWELEVE GRADE STUDENTS OF SMK MUHAMMADIYAH CANGKRINGAN IN ACADEMIC YEAR 2013/2014 - Riko Resbiantara; Samsul Hadi (Jurnal Taman Vokasi, 2014)
The objective of this study is to improve students’ activitity and achievement of kopling system service by using demonstration method with animation media in SMK Muhammadiyah Cangringan in the academic year 2013/2014. Type of this tudy was action research. The subject of this study was the tweleve grade students of SMK Muhammadiyah Cangkringan consisted of 24 students. To analyze the data, the researcher analyzsed the percesnatge of students’ activities and tests. This study shows that there was improvement of studenets’ activities by using demonstration method with animation media. It can be been from the result of tests of each cycle. The average score of test I was 63,13 and the students who were completed the study wer2 33,3%, while the average activities was 64,12%. The average score of tests II was 72,12 and the students who were completed the study were 66,6%, while the average activity was 79,94%. The average score of test II was 79,79 and the students who were completed the study were 87,5%, while the average activity was 90,84%.